2021
DOI: 10.1039/d0cp06471h
|View full text |Cite
|
Sign up to set email alerts
|

A ternary mixture at the border of Soret separation stability

Abstract: Ternary mixtures with the Soret effect are prone to triple-diffusive convection in a thermal field. The Soret coefficients of the toluene-methanol-cyclohexane mixture, measured in microgravity at a given composition [0.62-0.31-0.07]...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…29 Based on these data, the first numerical study of this mixture was devoted to revealing the flow patterns in a gravitational field in the geometry of the Soret cell. 30 The analysis revealed motionless, metastable, and convective patterns depending on initial temperature of the system. This work presents experimental, numerical and analytical study of concentration and flow patterns and their stability in toluene (T)-methanol (M)-cyclohexane (Ch) mixture in the geometry of thermogravitational column.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…29 Based on these data, the first numerical study of this mixture was devoted to revealing the flow patterns in a gravitational field in the geometry of the Soret cell. 30 The analysis revealed motionless, metastable, and convective patterns depending on initial temperature of the system. This work presents experimental, numerical and analytical study of concentration and flow patterns and their stability in toluene (T)-methanol (M)-cyclohexane (Ch) mixture in the geometry of thermogravitational column.…”
Section: Introductionmentioning
confidence: 98%
“…29 Based on these data, the first numerical study of this mixture was devoted to revealing the flow patterns in a gravitational field in the geometry of the Soret cell. 30 The analysis revealed motionless, metastable, and convective patterns depending on initial temperature of the system.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent studies have revealed many salient features of ternaries, such as the importance of the condition number for the optical contrast factor matrix 39,40 as well as the importance of cross-diffusion, which can lead to opposite signs of the Soret and thermodiffusion coefficients. 41 Still, there is a lack of studies, equally among binary and ternary mixtures, containing nanoparticles and, in particular, fullerene. Fullerene was discovered in 1985 while trying to understand how long carbon chains form in interstellar space.…”
Section: ■ Introductionmentioning
confidence: 99%
“…With the advent of convection-free microgravity environments, the focus of research has strongly shifted toward ternary mixtures. Recent studies have revealed many salient features of ternaries, such as the importance of the condition number for the optical contrast factor matrix , as well as the importance of cross-diffusion, which can lead to opposite signs of the Soret and thermodiffusion coefficients …”
Section: Introductionmentioning
confidence: 99%